FAKTOR PENYEBAB TERJADINYA EPILEPSI PADA PASIEN RAWAT JALAN DI POLI ANAK - Irma Fidora; Marizki Putri; Mahdalena Chaniago (STIKes Al-Insyirah Pekanbaru, 2021)
Epilepsy affects all levels of society globally with a relatively high incidence. Epilepsy also has an impact on the quality of life, daily activities, mental disorders, social environment and increasing death. This study was to determine the factors that cause epilepsy. Study determined the relationship between family history, pregnancy and childbirth history, and drugs with epilepsy. This type of research was correlation with cross sectional design. The population in this study was 102 people with a sample size of 31 people taken by accidental sampling. Collecting data used an instrument in the form of a questionnaire and analyzed using the Chi-Square test. The results showed that there was a relationship between family history and epilepsy with p value = (0.019), there was a relationship between pregnancy and childbirth history with epilepsy with a value of p = (0.008), there was a relationship between drug consumption and epilepsy with a value of p = (0.029). It can be concluded that there is a relationship with family history, history of pregnancy and childbirth, drug consumption with epilepsy.